2013
DOI: 10.1074/jbc.m112.418699
|View full text |Cite
|
Sign up to set email alerts
|

Essential Calcium-binding Cluster of Leptospira LipL32 Protein for Inflammatory Responses through the Toll-like Receptor 2 Pathway

Abstract: Background: LipL32 induces a renal cell inflammatory response through the TLR2-signaling pathway. Results: Ca 2ϩ -binding LipL32 mutants showed attenuated TLR2-mediated inflammatory responses. Conclusion:The Ca 2ϩ -binding cluster of LipL32 is essential in regulating its interaction with TLR2 for subsequent inflammatory response induction. Significance: This investigation provides significant evidence for crucial roles of the Ca 2ϩ -binding cluster of LipL32 for pathogenesis via association with TLR2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
65
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(70 citation statements)
references
References 40 publications
2
65
1
2
Order By: Relevance
“…During in vivo multiplication and invasiveness in the infected host, the non-surface-exposed Hap1/LipL32 is required at an early stage of infection for the binding of Leptospira spp to the ECM of target cells [14,26]. The "atypical polyD motif" [28] is specifically involved in binding Hap1/LipL32 to the well-conserved TLR2 during the first step of pathogen recognition [28][29][30]. This early recognition by innate immunity could thus explain the earlier production of anti-PP antibodies, compared to agglutinating antibodies, in dogs and humans [20].…”
Section: Discussionmentioning
confidence: 99%
“…During in vivo multiplication and invasiveness in the infected host, the non-surface-exposed Hap1/LipL32 is required at an early stage of infection for the binding of Leptospira spp to the ECM of target cells [14,26]. The "atypical polyD motif" [28] is specifically involved in binding Hap1/LipL32 to the well-conserved TLR2 during the first step of pathogen recognition [28][29][30]. This early recognition by innate immunity could thus explain the earlier production of anti-PP antibodies, compared to agglutinating antibodies, in dogs and humans [20].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it has been shown that the major protein LipL32 induces inflammatory responses through the Tolllike receptor 2 pathway in human renal cells (Lo et al, 2013). .…”
Section: Discussionmentioning
confidence: 99%
“…The portions responsible to bind the host lipid bilayer (noncontinuous b13-turn and C-terminal amphipathic a-6 helix), and the charged and hydrophilic amino acids were found to be important in therapeutic applications. Lo et al [28] studied the role of the calciumbinding site in the LipL32 on inflammatory response through Toll-like receptors (TLRs). Mutation-assisted studies indicated that the calcium interaction is necessary to maintain the structure of LipL32 and is a crucial factor in the interaction of LipL32 with TLR in renal cells.…”
Section: Therapeutic Applicationsmentioning
confidence: 99%